Enhancing irradiation tolerance via building 3D diffusion paths for He+ in multilayers by epitaxial growth. (September 2022) - Wan, Q.; Liu, Y.; Yang, B.; Zhang, J.; Xiao, Y.Y.; Liu, X.Q.
Graphical abstract: Highlights: TiSiN/CrN coatings with different Si and bias voltage have been deposited for He irradiation. Amorphization and bubbles were observed in irradiated coatings which led to softening effect and hardening effect, respectively. The layer interface could effectively increase the radiation tolerance of nano-amorphous coatings. Coherent interface formed by epitaxial growth reduced the bubble density at layer interface and lowered the risk of interface embrittlement. Abstract: Interface engineering such as grain refinement, multilayer structure was reported to be efficient strategy to enhance the irradiation tolerance by promoting the defects annihilation. However, rapid accumulation of helium atoms at interface would lead to high density bubbles and induce interface crack. In this study, we propose a new strategy to address the root causes of bubble formation by releasing He through the designed coherent interface (CI) which is formed by epitaxial growth between two sublayers without sacrifice the mechanical properties. To reveal the enhancement of CI on the irradiation tolerance, the mechanical properties and microstructure evolution of TiSiN/CrN multilayers have been investigated before and after He+ irradiation. TiSiN/CrN coatings reveal obvious amorphization at top-surface and large amount of bubbles have been observed at interfaces. The variation of hardness of the irradiated coatings depends on the competition between softening effect and hardening effect, induced by amorphization and bubble respectively. With the formation of CI across the sublayers, He atoms diffuse through the CI to deeper area beyond the ion projected range, decreasing density and size of the bubble at layer interface. Therefore, we present a new strategy of designing protective multilayer coatings for nuclear reactor through the introduction of CI.